MEDIASI DI MAHKAMAH SYAR’IYAH:KEGAGALAN DAN FAKTOR-FAKTORNYA - safriadi safri yadi (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2022)
This study aims to determine the background of the failure of mediation in the Syar'iyah Court and the factors causing it. This research uses the normative juridical method, namely legal research conducted based on the norms and rules of the legislation. Sources of data obtained from literature, books, and applicable legislation. Data analysis used descriptive analysis method. The results of the research that can be concluded are the factors that cause at least the successful mediation in the Syar'iyah Court: First, the state of the marital breakdown reported to the Court has been reconciled by other parties several times, so that the application of mediation in the Court is not effective. Second, the lack of judges who can become mediator judges. Third, the influence of some lawyers who prioritize their personal interests rather than resolving cases more quickly and at low costs. The failure of Mediation at the Syar'iyah Court is still relatively large, so cases at the Syar'iyah Court are still very dominant to continue the trial process to the next stage.